Analisis Sosiologis Terhadap Kejadian Konflik Berlatar Agama di Aceh - Saifullah, T; Alfikri, Albert (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research studies the role of the Acehnese local government in handling religious conflicts between Islamic sects. Sociologically, religious conflict can be defined as a dispute between two or more people over interests, goals, and understandings that bring religious doctrine as the reason for the conflict. A social conflict does not necessarily occur unless it begins with the presence of a potential lurking within the community and then escalates, heats up, becomes tension, and ultimately culminates in a physical conflict as a result of the presence of a trigger. In the context of Aceh, the religious conflict is revealed by the conflict between Islamic sects that manifests itself in cases of forced change of mosque management that is sometimes associated as a case of mosque seizure. Simply put, the purpose of this research is to see how the role of the Acehnese local government in handling religious conflicts among fellow Muslims that are squared in the sect. This study is a sociological study with a qualitative approach. The results of the study show that the conflict between Muslims in Aceh has occurred for a long time, ranging from the issue of wanting to establish an Islamic state with Islam as the concept of the country, to the issue of Islam which sect is more correct. This potential for conflict is seen recurrently in factual events such as feuds between Islamic sects.